Determinant Analysis Of Marine Fishermen's Income In Denpasar City - Renita Evelinda; Ni Nyoman Reni Suasih (Jurnal Syntax Transformation, 2023)
According to data from BPS Bali Province, Denpasar City's fishing production value is high, coming in at Rp943,607,030. Fishermen's income, however, is lower than that of farmers and artisans because it is based on the capital and operating expenses for each voyage. If supported by a relatively appropriate physical and financial infrastructure, processing of fish products will increase. In this study, the effects of capital, fishing experience, ship ownership status, working hours, and fish capture on marine fishermen's income were examined. Using the SPSS program, perform a multiple linear regression analysis on the data. With a sample size of 91 respondents, secondary and primary data were employed. The findings demonstrated that a number of factors, including money, fishing experience, ship ownership status, working hours, and fishing itself, have an impact on the revenue of marine fishermen in Denpasar City. While boat ownership status and working hours partially do not have a major impact on the income of marine fisherman in Denpasar City, capital, fishing experience, and fish catches do have a big impact.